Dasar Pengelompokan Surah Makkiyyah dan Madaniyyah dalam Mushaf Standar Indonesia - Reflita Reflita (SUHUF, 2010)
Difference of opinion among the muslim scholars concerning the number of verses and chapter of makkiyyah and madaniyyah is not the new issue. The difference can be seen from the difference of the group of one verse which is available in the Qur'an, or in some books of Qur'anic exegesis available. In the Standard Qur'an of Indonesia being published by the Ministry of Religious Affairs, the Republic of Indonesia, there are also some inconsistensies in putting the group of the chapter in accord with the development of study toward this verse or chapter of makkiyyah and madaniyyah. Theoritical study concern-ing this science is extremely needed to be the reference in putting the gorup of the chapter in the Qur'an.